Keanekaragaman Kupu-Kupu di Kawasan Gunong Bonsu Kabupaten Rokan Hulu, Provinsi Riau - BIBAS, ELPE; MUHAMMAD, AHMAD; SALBIAH, DESITA (Jurusan Biologi FMIPA Universitas Riau, 2016)
This study concerned the species diversity and abundance of butterflies in Gunong Bonsu, an area situatedin Rokan Hulu District, Riau Province. Sampling was conducted within the period of Januari-April 2015in four different habitat types, i.e. secondary forest, rubber jungle, palm oil plantation and tour sites. Twostandardized sampling methods were combined, i.e. sweeping and trapping using fruit bait along transect(100 m-long fixed transect in each selected site). A total of 1641 individuals were captured with 189butterflies species were identified, including 14 species of Papilionidae, 105 species of Nymphalidae, 19species of Pieridae, 14 species of Lycaenidae, and 19 species of Hesperiidae. Among these species, onlyTroides amphrysus (birdwing butterfly) which is protected by the law at national as well as internationallevel. The species diversity index for Gunong Bonsu area is very high (Hâ= 4,53).Keywords: abundance, butterflies, species diversity index